2016
DOI: 10.1093/glycob/cww059
|View full text |Cite
|
Sign up to set email alerts
|

The structural investigation of glycosaminoglycan binding to CXCL12 displays distinct interaction sites

Abstract: The stromal cell-derived factor 1α (CXCL12) belongs to the CXC chemokine family and plays an important role in tissue regeneration and the recruitment of stem cells. Here, a stable chemotactic gradient is essential that is formed by the interaction of CXCL12 with the extracellular matrix. Binding properties of CXCL12 to naturally occurring glycosaminoglycans (GAGs) as well as to the artificial highly sulfated hyaluronic acid (HA) are investigated by using a combination of NMR spectroscopy, molecular modeling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 84 publications
2
31
0
Order By: Relevance
“…Ten extracellular proteins involved in the regulation of tissue and bone healing, which are accumulated or released by interactions with GAG, were selected as representative examples. As cytokines interleukin 8 (IL-8/CXCL-8), responsible for neutrophil recruitment to guide inflammation,16 the pro- and antiinflammatory interleukin 10 (IL-10),5 d stromal cell-derived factor 1 (SDF-1/CXCL-12), responsible for MSC attraction,17 and transforming growth factor β1 (TGF-β1) as key mediator in several phases of the healing process were chosen 18. As examples of growth factors served the strongly mito- and angiogenic fibroblast growth factors 1 and 2 (FGF-1, FGF-2)19 and the osteoinductive bone morphogenetic protein-2 (BMP-2) 20.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten extracellular proteins involved in the regulation of tissue and bone healing, which are accumulated or released by interactions with GAG, were selected as representative examples. As cytokines interleukin 8 (IL-8/CXCL-8), responsible for neutrophil recruitment to guide inflammation,16 the pro- and antiinflammatory interleukin 10 (IL-10),5 d stromal cell-derived factor 1 (SDF-1/CXCL-12), responsible for MSC attraction,17 and transforming growth factor β1 (TGF-β1) as key mediator in several phases of the healing process were chosen 18. As examples of growth factors served the strongly mito- and angiogenic fibroblast growth factors 1 and 2 (FGF-1, FGF-2)19 and the osteoinductive bone morphogenetic protein-2 (BMP-2) 20.…”
Section: Resultsmentioning
confidence: 99%
“…Blind docking was applied in order to predict potential recognition sites for the sulfated oligohyaluronans 15 , 16 and 19–26 on the surface of the target proteins IL-8, IL-10, BMP-2 and sclerostin. MD simulations were used to refine the resulting GAG–protein complexes and to obtain binding energies (including per residue and pairwise interactions) and atomic-detailed information about the established interactions in order to rationalize the mechanisms involved in GAG–protein recognition 5c,7b,c,8,17,29. The results obtained for IL-8 and Sclerostin are discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…Both N‐ and C‐terminally truncated IL‐8 mutants were investigated by analytical Hep affinity chromatography and surface plasmon resonance (SPR) in terms of their ability to bind GAGs. Previously, it was shown that not only the net sulfation determining overall electrostatic interactions in the system but the type of glycosidic linkage and the particular sulfation pattern of GAGs can affect affinity and specificity of the binding in protein‐GAG systems . Recent findings suggested that the binding in protein‐GAG systems could be either highly specific or generally unspecific .…”
Section: Resultsmentioning
confidence: 99%
“…Our current studies and previous studies of hNACs show that residues from the N-loop and 40s loop also determine binding, that their contributions can be quite significant, and that the binding geometries can be quite diverse (24, 26 -29). Recent NMR studies of GAG binding of chemokines CXCL10, CXCL12, and CXCL13 also show diverse binding interfaces and geometries (41)(42)(43)(44). Considering all chemokines bind GAGs, it is very likely that each chemokine shows distinct GAG interactions.…”
Section: Discussionmentioning
confidence: 99%